2023
DOI: 10.29333/ejmste/12838
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of factors influencing career choice among STEM undergraduates in Nigeria universities

Abstract: Shortage of expertise in science, technology, engineering and mathematics (STEM) fields have been reported over the years despite financial and social interventions by government through policies and efforts of stakeholders. Remediating the afore stated requires a retrospection into the factors responsible for learners’ choice and career orientation in STEM. As such, this study investigated undergraduates’ choice of STEM field and career orientation employing descriptive research. Undergraduates’ choice of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
2
1
0
Order By: Relevance
“…This finding aligns with Betz and Klein (1996), who proposed that career decision outcomes and expectations often lead to career decision-making and career development behaviours (Lent et al. , 2000; Badmus and Jita, 2023). Greenhaus et al .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This finding aligns with Betz and Klein (1996), who proposed that career decision outcomes and expectations often lead to career decision-making and career development behaviours (Lent et al. , 2000; Badmus and Jita, 2023). Greenhaus et al .…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, rewards and recognition are the outcomes one expects before taking a career decision. This finding aligns with Betz and Klein (1996), who proposed that career decision outcomes and expectations often lead to career decision-making and career development behaviours (Lent et al, 2000;Badmus and Jita, 2023). Greenhaus et al (1983) researched similar variables and found that students' career decisions are significantly impacted by their satisfaction with their chosen careers and the likelihood that their chosen profession would provide specific rewards, especially financial remuneration (Akosah-Twumasi et al, 2018), which is also found to be one of the most influential extrinsic factors of career choice decision.…”
Section: Discussionsupporting
confidence: 66%
“…STEM education remains vital for improved economic development for international competitiveness, job creation and economic relevance (Badmus and Jita, 2023;Baiduc et al, 2016;Ismail et al, 2019). Despite this importance, the teaching and learning of STEM especially at public universities have been plagued with challenges which span from sociocultural issues, teaching resources, basic infrastructures, time allocation and disruption, poor financing and attitude to learning among others (Fong and Kremer, 2020;Fomunyam, 2019).…”
Section: Problem Statementmentioning
confidence: 99%